Controlling Internal Pore Sizes in Bicontinuous Polymeric Nanospheres1. (16th January 2015) - McKenzie, Beulah E.; Friedrich, Heiner; Wirix, Maarten J. M.; de Visser, Joël F.; Monaghan, Olivia R.; Bomans, Paul H. H.; Nudelman, Fabio; Holder, Simon J.; Sommerdijk, Nico A. J. M.
Abstract Complex polymeric nanospheres were formed in water from comb‐like amphiphilic block copolymers. Their internal morphology was determined by three‐dimensional cryo‐electron tomographic analysis. Varying the polymer molecular weight (MW) and the hydrophilic block weight content allowed for fine control over the internal structure. Construction of a partial phase diagram allowed us to determine the criteria for the formation of bicontinuous polymer nanosphere (BPN), namely for copolymers with MW of up to 17 kDa and hydrophilic weight fractions of ≤0.25; and varying the organic solvent to water ratio used in their preparation allowed for control over nanosphere diameters from 70 to 460 nm. Significantly, altering the block copolymer hydrophilic–hydrophobic balance enabled control of the internal pore diameter of the BPNs from 10 to 19 nm.